ANALISIS KELAYAKAN USAHA AGROINDUSTRI KOPI LUWAK DI KECAMATAN BALIK BUKIT KABUPATEN LAMPUNG BARAT - Pahlevi, Rico; Zakaria, Wan Abbas; Kalsum, Umi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The study aimed to analyze the financial feasibility of luwak coffee agroindustry. The research was conducted at Balik Bukit district of West Lampung Regency. This location was selected purposively. The research used primary and secondary data. The research samples were 2 agro industries which were chosen purposively. The data was collected in Oktober to November 2012. The financial feasibility was analyzed by NPV, IRR, Net B/C, Gross B/C, Payback Period, BEP and sensitivity. The results showed that small and micro agroindustries of luwak coffee at Balik Bukit District of West Lampung Regency were financially feasible and profitable to be developed, the increase of cost and decrease of product’s price influenced the luwak coffee agro industries. Keywords: financial feasibility, macro agroindustry, luwak coffee, small agroindustry